SISTEM INFORMASI PENJUALAN BBM/PELUMAS BERBASIS WEB (Studi kasus pada PT. PERTAMINA Semarang) - SamiinTarnomo, SamiinTarnomo (LPPM Universitas Sains dan Teknologi Komputer, 2022)
In the reform era the world development changes very rapidly, free trade is wide open and businesses similar to PT. Pertamina also started a lot. PT. Pertamina began to use several marketing strategies, including through marketing personnel and occasional advertisements in print media. Based on the marketing strategy used, it turns out that it has not yet achieved satisfactory results. This condition is supported by information for consumers to get to know PT. Pertamina more broadly. Based on data and facts obtained from PT. Pertamina Semarang sales of fuel and lubricants have not been satisfactory and are still as stable as the previous years. This condition causes PT. Pertamina Semarang intends to increase sales of fuel and lubricants more widely. Another obstacle is the problem of selling fuel and lubricants at PT. Pertamina Semarang is a service to facilitate the purchase of fuel and lubricants for consumers who have locations outside the city are still lacking. So far, services for consumers who are outside the city only by telephone or fax machine.